Modernization, Awareness, and Compliance: A Behavioral Study of Motor Vehicle Taxpayers in Tangerang - Rismawandi (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Taxpayer compliance represents a fundamental aspect of a sustainable taxation system. This study investigates the influence of tax administration modernization, taxpayer knowledge, taxpayer awareness, and administrative sanctions on motor vehicle taxpayer compliance at the One-Stop Administration Services Office in Ciledug, Tangerang City. The research employed a quantitative explanatory design with multiple linear regression analysis. Primary data were collected through questionnaires distributed to 88 purposively selected respondents. The results reveal that modernization of the tax administration system, taxpayer knowledge, and administrative sanctions have no significant effect on compliance, while taxpayer awareness shows a positive and significant influence. These findings highlight that compliance is shaped more by intrinsic awareness and moral responsibility than by technical modernization or punitive measures. Thus, policy efforts should focus on strengthening taxpayer awareness and internal motivation as the foundation for improving voluntary compliance.